Introduction - Shamsuddin M. (My University, 2025)
Metals generally occur in combined states in the form of ores and minerals as oxides, for example, cassiterite (SnO2), cuprite (Cu2O), chromite (Feo·Cr2O3), hematite (Fe2O3), pyrolusite (MnO2), rutile (TiO2), wolframite [Fe(Mn)WO4]; sulfides, for example, chalcopyrite (CuFeS2), cinnabar (HgS), galena (PbS), molybdenite (MoS2), pentlandite [(NiFe)9S8], sphalerite (ZnS), stibnite (Sb2S3); silicates, for example, beryl (3BeO·Al2O3·6SiO2), zircon [Zr(Hf)SiO4]; titanate, for example, ilmenite (FeO·TiO2); carbonates, for example, azurite [2CuCO3·Cu(OH)2], dolomite (MgCO3·CaCO3), malachite [CuCO3·Cu(OH)2], magnesite (MgCO3); phosphate, for example, monazite [Th3(PO4)4]; vanadate, for example, carnotite (K2O·2UO3·V2O5) and so on. A few precious metals like gold, silver, and platinum are found in the native or uncombined form because they are least reactive. As naturally occurring ores and minerals are associated with gangue such as silica, alumina, etc., the first step in the extraction of metals is the removal of gangue from the ore containing the metal value by mineral beneficiation methods incorporating comminution, preliminary thermal treatment and concentration by magnetic separation, heavy media separation, jigging, tabling, and flotation. The choice of the method depends upon the nature of the gangue and its distribution in the ore and the degree of concentration of the metal value required, which depends on the extraction technology to be adopted. The extraction methods incorporate various steps to obtain the metal from the concentrate, ore or some mixture, or from chemically purified minerals; occasionally, the mineral may be first converted to a more amenable form. The mineral beneficiation step lies between mining and extraction. The extraction processes are classified into three main groups, namely: © 2021, The Minerals, Metals & Materials Society.